2022
DOI: 10.1002/joc.7546
|View full text |Cite
|
Sign up to set email alerts
|

Climatology and extreme cases of sea‐effect snowfall on the southern Baltic Sea coast

Abstract: Heavy snowfall events of possible sea‐effect origin, occurring on the southern Baltic Sea coast, are described in this study. The analysed region is not very snowy, with an average of 40 days with snow cover in the winter season and a mean maximum snow depth of 8–12 cm. Twenty‐five snowfall events were selected using the threshold of 20 cm/2 days (i.e., 20 cm of snow depth increase during 2 days), and the synoptic climatology, as well as triggering factors of their occurrence, were defined. The bipolar pattern… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 51 publications
(79 reference statements)
0
2
0
Order By: Relevance
“…Recent study by Bednorz et al . (2022) produced climatology of extreme cases of sea‐effect snowfall on the southern Baltic Sea coast. They found out that temperature difference between SST and T850 was over 15°C when snowfall accumulated at least 20 cm/2 day of new snow.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Recent study by Bednorz et al . (2022) produced climatology of extreme cases of sea‐effect snowfall on the southern Baltic Sea coast. They found out that temperature difference between SST and T850 was over 15°C when snowfall accumulated at least 20 cm/2 day of new snow.…”
Section: Discussionmentioning
confidence: 99%
“…Climatology of extreme snowfall cases (>20 cm/2 day) on the Polish Baltic Sea coast for 1981–2020 revealed that most of those cases resulted from sea‐effect snowfall (Bednorz et al ., 2022). In addition, occurrence of atmospheric parameters favouring snowband formation in the east coast of Sweden have been studied from 1970 to 2099 with the aid of a coupled regional atmosphere‐ice‐ocean model RCA4‐NEMO (Dieterich et al ., 2020).…”
Section: Introductionmentioning
confidence: 99%